Invest, expropriate, or wait? Expected income and the demand for redistribution - Philipp Harms; Stefan Zink (Universität Konstanz, Fachbereich Wirtschaftswissenschaften, 2000)
In this paper we offer an explanation why a poor majority does not necessarily expropriate a rich minority. We present a dynamic model in which individuals are willing to accept an unequal distribution of income in the current period if they are sufficiently optimistic about their future economic prospects. In this case, the fact that a policy of radical redistribution inflicts a persistent damage on the economy and thus reduces agents' future earning possibilities prevents the poor from expropriating the rich. Unlike previous contributions, we do not assume exogenous changes of the income distribution, but relate such changes to agents' rational investment decisions.
Keywords: D31; D72; P16; 330; political economy; inequality; redistribution of income